Synthesis of lower olefins by hydrogenation of carbon dioxide over supported iron catalysts - Wang, Jingjuan; You, Zhenya; Zhang, Qinghong; Deng, Weiping; Wang, Ye (Catalysis today, 2013)
•K+ is an efficient promoter of Fe catalysts for CO2 hydrogenation to lower olefins.•ZrO2 is an efficient support for the selective formation of olefins.•K+ accelerated the generation of χ-Fe5C2 under reaction conditions.•K+ enhanced the adsorption of CO2 and decreased the hydrogenation ability The hydrogenation of carbon dioxide to lower (C2–C4) olefins is an important reaction for the utilization of CO2 as a carbon feedstock for the production of building-block chemicals. We found that an Fe/ZrO2 catalyst could catalyze the hydrogenation of CO2, but the main products were CH4 and lower (C2–C4) paraffins. The modification of the Fe/ZrO2 catalyst by alkali metal ions except for Li+ significantly decreased the selectivities to CH4 and lower paraffins and increased those to lower olefins and C5+ hydrocarbons, particularly C5+ olefins. The modification by Na+, K+, or Cs+ also increased the conversion of CO2. The best performance for lower olefin synthesis was obtained over the K+-modified Fe/ZrO2 catalyst with a proper K+ content (0.5–1.0wt%). Among several typical supports including SiO2, Al2O3, TiO2, ZrO2, mesoporous carbon, and carbon nanotube, ZrO2 provided the highest selectivity and yield to lower olefins. Our characterizations suggest that the modification by K+ accelerates the generation of χ-Fe5C2 phase under the reaction conditions. This together with the decreased hydrogenation ability in the presence of K+ has been proposed to be responsible for the enhanced selectivity to lower olefins.